Nano-targeting vascular remodeling in cancer: Recent developments and future directions. (November 2022) - Giordo, Roberta; Wehbe, Zena; Paliogiannis, Panagiotis; Eid, Ali H.; Mangoni, Arduino A.; Pintus, Gianfranco
Abstract: Tumor growth and progression are strictly dependent on the adequate blood supply of oxygen and nutrients. The formation of new blood vessels and vascular networks is essential to ensure this demand. Blood vessels also facilitate the invasion of cancer cells into nearby tissues and their subsequent metastasis. Tumor cells represent the main driver of the neovascularization process through the direct or indirect, by neighboring non-cancer cells, release of pro-angiogenic molecules. The mediators (e.g., growth factors and extracellular matrix components), signaling pathways, cellular components, and processes (e.g., endothelial cell proliferation and migration) activated in tumor angiogenesis are similar to those involved in normal vascular development, except they lack efficient control mechanisms. Consequently, newly formed tumor vessels are typically fragile and hyperpermeable with a reduced and erratic blood flow. Targeting the tumor vasculature has been the focus of intense research over the last 20 years. However, despite the initial interest and expectations, the systemic use of anti-angiogenic drugs has not always led to therapeutic breakthroughs and, in some cases, has been associated with the development of tumor adaptive resistance resulting in a more aggressive phenotype. Therefore, new therapeutic approaches have focused on combining anti-angiogenic agents with chemotherapy or immunotherapy and/or optimizing (normalizing) the structure and function of tumor blood vessels to ensure a more efficient drug delivery. In this context, nanomedicine offers the significant advantage of targeting and releasing anti-angiogenic drugs at specific sites, minimizing toxicity in healthy tissues. Several nanoparticles possess intrinsic modulatory effects on angiogenesis, while others have been developed to facilitate drug delivery in association with chemotherapy, thermotherapy, radiotherapy or in response to specific stimuli within the tumor environment (e.g., enzymes, ions, redox potential) or exogenous stimuli (e.g., temperature, electricity, magnetic fields, and ultrasound). Other nanoparticles can modify, under specific conditions, their physical properties (e.g., dimensions, structure, and interactions) to increase penetration in tumor cells. This review provides a comprehensive appraisal of the critical modulators of tumor vascular biology, the most promising nano-strategies that specifically target such modulators, and the directions for future research and clinical applications.